Pengembangan Model Perencanaan Alokasi Pesanan Pada Fungsi Koordinasi Produksi Untuk Meminimasi Biaya Produksi Dan Biaya Pengiriman - Arief Suardi Nur Chairat; Vendy Antono (JURNAL POWERPLANT, 2016)
In many real situations, the estimated demand is very uncertain. This uncertainty has the tendency to greater degree for next coming period of time. Inefficiency of order management can give impact to customer service, order cycle time and operational costs for an order. Order management is a series of related to the management of customer orders using the standard order document. The main focus of this research is the development model of the planning system in coordination function to allocate production orders into the use of different capacities. The test uses three different distribution and calculating the total cost for 30 periods. The goal is to achieve an efficient and effective system taking into account the availability of generating capacity and minimize total costs of production and delivery. Based on experiments with a number of orders, the calculation of the total cost of the proposed method in accordance with the total cost equation. The total cost of the trial simulation on each distribution is influenced by the number of demands in each period.